Relevance of Germline Mutation Screening in Both Familial and Sporadic Head and Neck Paraganglioma for Early Diagnosis and Clinical Management - Mario A. Hermsen; María A. Sevilla; José Luis Llorente; Marjan M. Weiss; Anneliese Grimbergen; Eva Allonca; Cristina Garcia-Inclán; Milagros Balbín; Carlos Suárez (Cellular Oncology)
Background: Head and neck paraganglioma (PGL) are benign tumors that can cause important direct or surgery induced morbidity. Almost all familial and 11–29% of sporadic PGL are caused by inactivating germline mutations in succinate dehydrogenase (SDH) genes. Our aim was to screen for such mutations and to evaluate clinical parameters as predictors of germline mutation.